Adaptive Neuro Fuzzy Prediction of Behavior of NSM Strengthened RC Beams - ناصر, عصام; حويجة, بسام; مبارك, ثراء (Latakia University Journal -Engineering Sciences Series, 2021)
The Near Surface Mounted (NSM) technique is a promising strengthening approach, though unpopular due to reliable serviceability prediction options. In this paper, a soft computing technique based on ANFIS is employed to predict the deflection and cracking behavior of NSM strengthened RC beams. The ANFIS results were compared with the experimental results and results of FIS, ANN approaches. The study indicated that the predicted deflection and crack width closely conform to the experimental results, which affirms the performance of the ANFIS model, this model demonstrated the superior predictive accuracy and capability of generalization over the fuzzy logic and artificial neural network (ANN) approaches